Hubungan Pendidikan, Pengetahuan dan Peran Tenaga Kesehatan dengan Penggunaan Kontrasepsi Intra Uterine Device (IUD) di Wilayah Kerja Puskesmas Rawat Inap Muara Fajar Pekanbaru - Risa Pitriani (Jurnal Kesehatan Komunitas, 2015)
Family planning programs provides contraceptive methodes, one of them is IUD. Based on data from two (2) years ago, acceptors used IUD in Health Center of Muara Fajar in 2011 were 0%, meanwhile in 2012 the use of contraceptive IUD is 0.33%. The aim of this research is to determine the relationship of education, knowledge and the role of health worker with the use of IUD in the health centers area of Muara Fajar Pekanbaru 2013. This research is a quantitative research with cross sectional analytical study design. The study population was all family planning acceptors in health centers area of Muara Fajar Pekanbaru with sample is 158 acceptors. Data collected by using primary data were analyzed with chi square test. The results showed that there is a correlation with education (p value = 0.001), knowledge (p value = 0.036) and the role of health workers with (p value = 0.034) with the use of IUDs. Advice for health workers by increasing counseling about contraception on an ongoing basis, either individually or in groups, on various types of contraceptives to increase knowledge